Drivers of elderly rail service passenger satisfaction: The roles of service innovation, perceived value and service quality - Ratchaphong Lieophairot; Nuttawut Rojniruttikul; Singha Chaveesuk (International Journal of Innovative Research and Scientific Studies, 2025)
This study investigates the factors influencing elderly rail passenger satisfaction (EPS). These include service innovation (SI), perceived value (PV), and passenger service quality (PSQ). The study also develops a structural equation model (SEM) representing SRT service EPS and validates the model using empirical data. The quantitative survey used a five-level Likert-scale questionnaire. The sample consisted of 625 elderly individuals with prior experience using Thailand's railway services, selected through multi-stage random sampling. Instrument reliability and validity were confirmed. Data analysis included descriptive statistics and confirmatory factor analysis using LISREL 9.2 to test measurement and structural models. Results indicated that older passengers rated SI, PV, PSQ, and EPS at high levels. The SEM demonstrated excellent fit with empirical data and accounted for 74% of the variance in EPS. The measurement model strongly aligned with theoretical expectations. The model was validated as a comprehensive framework in understanding railway services' EPS, highlighting the significance of SI and PV. These insights offer a foundation for enhancing user experience among aging populations. The findings guide railway operators and policymakers seeking to improve public transport inclusivity, especially among elderly users in Thailand’s rapidly aging society.
Keywords: Customer Service Quality and Loyalty; Sharing Economy and Platforms; Consumer Retail Behavior Studies